Beneficial effects of tonsillectomy plus steroid pulse therapy on inflammatory and tubular markers in patients with IgA nephropathy - Maruyama, Shuntaro (Kidney Res Clin Pract, 2016)
BACKGROUND: IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide. Tonsillectomy plus steroid pulse therapy has been able to induce clinical remission in early-stage IgAN. However, its possible effect on systemic and local cytokines and tubular markers has not been fully investigated. METHODS: We obtained serum and urine samples from 38 patients just before renal biopsy and third steroid pulse therapy. Markers of tubular damage such as N-acetyl-β-d-glucosaminidase, and kidney injury molecule-1 and inflammation such as interleukin (IL)-6, monocyte chemotactic protein (MCP)-1, intercellular adhesion molecule (ICAM)-1, and vascular cell adhesion molecule (VCAM)-1 were measured by immunoassay. RESULTS: Before renal biopsy, only urinary inflammatory markers, except MCP-1, were associated with glomerular (proteinuria) and/or tubular damage markers. Proteinuria, hematuria, and estimated glomerular filtration rate dramatically improved after therapy. In addition, levels of serum IL-6 and ICAM-1 and all urinary markers declined significantly; however, serum MCP-1 and VCAM-1 levels did not. None of the urinary markers correlated with the serum inflammatory markers. CONCLUSION: Tonsillectomy plus steroid pulse therapy for patients with IgAN might be useful for improving not only glomerular damage marker but also tubular damage markers through the improvement of local renal inflammation.